2016
DOI: 10.1016/j.ijgo.2015.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from cluster surveys on the association between home‐based counseling and use of family planning in conflict‐affected Darfur

Abstract: After the introduction of home-based FP counseling for couples and FP services in clinics, women's awareness and use of modern FP methods increased in a conflict-affected setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“… 16 A study of high quality assessing a home-based counselling and awareness programme for internally displaced women in Sudan led to an increase in the use of modern family planning methods (adjusted OR (aOR) 2.8, 95% CI 2.0 to 4.1). 27 Another study of high quality assessed a refugee-led reproductive health group operating across 48 Guinean refugee camps. 25 The intervention recruited refugee nurses and midwives to local health facilities, trained lay women to provide health education and contraception and to facilitate referrals.…”
Section: Resultsmentioning
confidence: 99%
“… 16 A study of high quality assessing a home-based counselling and awareness programme for internally displaced women in Sudan led to an increase in the use of modern family planning methods (adjusted OR (aOR) 2.8, 95% CI 2.0 to 4.1). 27 Another study of high quality assessed a refugee-led reproductive health group operating across 48 Guinean refugee camps. 25 The intervention recruited refugee nurses and midwives to local health facilities, trained lay women to provide health education and contraception and to facilitate referrals.…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] A home-based counselling and awareness programme for internally displaced women in Sudan led to an increase in the use of modern family planning methods (aOR 2.8, 95% CI 2.0, 4.1). [ 27 ] A programme of mobile outreach and public health strengthening in Uganda led to an increase in the number of women who reported ever using a family planning method (aOR 2.23, 95% CI 1.7, 2.92, P<0.001), and a reduction in the unmet need for family planning from 52.1% to 35.7% (aOR 0.47, 95% CI 0.37, 0.6, P<0.001). [ 26 ] A study in Pakistan providing subsidised healthcare to refugees reported use of contraceptives in the subsidised group (54%) was more than double the use reported in the non-subsidised group (25%), (P<0.001), and reported that the non-subsidised group was more likely to use the oral contraceptive pill (40.7%), whereas the subsidised group was more likely to have tubal ligation (36.7%) (p<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…One study on the association between home-based counselling and use of FP reported that the proportion of women receiving home-based FP counselling increased from 7.3% to 59.8%, and those aware of modern FP methods increased by over 20%. 35 Wayte et al, 63 however, reported fewer women received FP and antenatal care (ANC) in camps, yet ANC uptake was higher compared to other MCH services. Also, obstetric care provided in the study by Mullany et al 51 showed significant uptake, especially among women with recent pregnancies.…”
Section: Sexual Reproductive Maternal and Child Health Interventionsmentioning
confidence: 99%
“…38 Sexually transmitted diseases (STIs) and HIV/AIDS were not a major focus in the SRH interventions. 35,38,51,57,63 Most interventions lasted for longer durations (up to three years) 35,51 compared to other intervention types. Reasons given for shorter SRH intervention periods included poor sustainability and high-cost implications.…”
Section: Sexual Reproductive Maternal and Child Health Interventionsmentioning
confidence: 99%